2018
DOI: 10.1111/ans.14765
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgery for hilar cholangiocarcinoma: state of art and future perspectives

Abstract: Minimally invasive surgery for HCCA is restricted to highly selected cases and is deemed technically achievable in experienced hands. However, technical and instrumental improvement is needed to reduce the relevant morbidity and popularize the use of minimally invasive surgery to treat HCCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
(46 reference statements)
1
22
0
2
Order By: Relevance
“…The meta-analyses published by Qiu et al[72] and Montalti et al[73] had also drawn similar conclusions. In addition, the meta-analysis published by Hu et al[74] in 2018 that analyzed the efficacy of robotic surgery in liver tumors also obtained similar conclusions. The analysis also found that the robotic group had a longer postoperative fasting time (weighted MD = 1.2, 95%CI: 0.24, 2.17), but the two groups showed no significant difference postoperative mortality (OR = 0.67, 95%CI: 0.16, 2.83).…”
Section: Methodssupporting
confidence: 53%
“…The meta-analyses published by Qiu et al[72] and Montalti et al[73] had also drawn similar conclusions. In addition, the meta-analysis published by Hu et al[74] in 2018 that analyzed the efficacy of robotic surgery in liver tumors also obtained similar conclusions. The analysis also found that the robotic group had a longer postoperative fasting time (weighted MD = 1.2, 95%CI: 0.24, 2.17), but the two groups showed no significant difference postoperative mortality (OR = 0.67, 95%CI: 0.16, 2.83).…”
Section: Methodssupporting
confidence: 53%
“…[14][15][16][17]20 Hence, many surgeons still elect to approach these procedures via the traditional open approach. Presently, with advancements in surgical technique and technology, increasing reports of laparoscopic bilio-enteric anastomosis for various indications such as choledochal cysts and bile duct cancers, [10][11][12]22 have been reported in the literature. Although good results with bilio-enteric anastomosis have been reported with conventional laparoscopy by high-volume expert surgeons, 10,33 questions remain about the transferability of these results.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 However, its use is mainly limited to relatively straightforward conditions such as biliary colic, symptomatic gallstones and early acute cholecystitis. The use of the laparoscopic approach for even more complicated major biliary surgeries such as for gallbladder cancer, [19][20][21] choledochal cysts, 9,10,12 bile duct cancers 22 and bile duct injuries 23 remain highly limited and is largely performed in a selected few high-volume specialized centres. The use of the laparoscopic approach for even more complicated major biliary surgeries such as for gallbladder cancer, [19][20][21] choledochal cysts, 9,10,12 bile duct cancers 22 and bile duct injuries 23 remain highly limited and is largely performed in a selected few high-volume specialized centres.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations